A Retrospective Analysis of Device Closure in Congenital Heart Disease: Experience from a Single Center - Bhatnagar, Sumit; Kinare, Amit; Ninama, Sneha (Journal of Neonatal Surgery, 2025)
Introduction:Congenital heart diseases (CHDs) are the most common congenital anomalies, affecting nearly 1% of live births. Traditionally managed through open-heart surgery, recent advances have led to widespread adoption of transcatheter device closure for selected lesions such as patent ductusarteriosus (PDA), atrial septal defect (ASD), and ventricular septal defect (VSD). This study aims to assess utilization patterns and clinical outcomes of device closures in CHDs, with emphasis on PDA. Methods:This retrospective observational study was conducted at a single tertiary cardiac center from January 2023 to December 2024. All pediatric and adult patients who underwent successful transcatheter device closure for PDA, ASD, or VSD were included. Data regarding defect type, device type (Amplatzer or Cocoon), and procedure-related outcomes were collected. Comparative analysis was performed between surgical and device closures using descriptive statistics and chi-square tests for significance. Results:Out of 99 procedures, 53 were device closures and 46 were surgical. No significant differences were found in age and sex distribution. Device closure was associated with shorter procedure time (p=0.002), minimal blood loss (p=0.003), early mobilization (p=0.002), and avoidance of sternotomy and cardiopulmonary bypass. Postoperative complications, including wound infection (p=0.000), bleeding (p=0.000), and ICU stay (p=0.002), were significantly lower in the device group. PDA cases showed the highest rate of device closure. Conclusion:Transcatheter device closure offers a safer, less invasive alternative to surgery in selected CHD cases, particularly PDA. Its favorable procedural profile and low complication rates support broader adoption in suitable patients